Plants vs. zombies. 3, Bully for you - Tobin, Paul 1965- (Dark Horse Books, 2015)
"Young adventurers Patrice and Nate have followed neighborhood defender Crazy Dave throughout time--but are they ready to investigate a school campus to keep the streets safe from zombies? In Plants vs. Zombies: Bully For You, they'll be visiting a very strange college in an attempt to take down Dr. Zomboss yet again--and any school visit's tolerable if you get to battle zombies! Paul Tobin (Prometheus, Bandette) and Ron Chan (The Guild, X-Men) join forces with the mysterious Anti-Bully Squad to deliver a hilarious, all-ages romp to your school! Featuring special bonus stories illustrated by acclaimed creators Dustin Nguyen, Jennifer Meyer, and Peter Bagge!"--Amazon.com.